ATLAS NAMA-NAMA DAERAH DALAM AL-QUR’AN - Khairat, Nurul; Fauzi; Erida (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2024)
This research is motivated by the issues that occur in Palestine until now. Is Palestine mentioned directly in the Qur'an or not. To find out this, no reference was found to answer the question. So, this research aims to index the names of regions that are mentioned directly in the Qur'an. The type of research used is development research (Research and Development) which aims to produce an Atlas of Regional Names in the Qur'an product. The results showed that the product produced had met the validity criteria, as evidenced by the assessment by the validator obtaining an A which means very good. Next, this product was tested on two groups of respondents, namely small groups and large groups. The results of the trial in the small group showed a percentage of 90.28% and in the large group 92.57%. Based on the results of the trials of the two groups, it can be concluded that the Atlas product of Regional Names in the Qur'an obtained very good percentage criteria. So, this product has been declared valid, practical, effective, and efficient.